How Can a Negative Magnetic Helicity Active Region Generate a Positive Helicity Magnetic Cloud? - Chandra, R. (2009)
The geoeffective magnetic cloud (MC) of 20 November 2003 was associated with the 18 November 2003 solar active events in previous studies. In some of these, it was estimated that the magnetic helicity carried by the MC had a positive sign, as did its solar source, active region (AR) NOAA 10501. In this article we show that the large-scale magnetic field of AR 10501 has a negative helicity sign. Since coronal mass ejections (CMEs) are one of the means by which the Sun ejects magnetic helicity excess into interplanetary space, the signs of magnetic helicity in the AR and MC must agree. Therefore, this finding contradicts what is expected from magnetic helicity conservation. However, using, for the first time, correct helicity density maps to determine the spatial distribution of magnetic helicity injections, we show the existence of a localized flux of positive helicity in the southern part of AR 10501. We conclude that positive helicity was ejected from this portion of the AR leading to the observed positive helicity MC.